De boa intenção o inferno está cheio: antecedentes e emissores que influenciam o comportamento dos jovens conversarem com a família sobre doação de órgãos - Silva Júnior, Severino Domingos (2020)
One of the key points to reduce the waiting list for organ donors is to promote campaigns to communicate the need to talk about organ donation in families. That said, we recognize that the Transformative Consumer Research (TCR) can play an important role in solving this problem, adopting this conceptual perspective to analyze the importance of elucidating which are the main variables that can influence the behavior of talking to the family about the donation of organs. To this end, we propose and test a theoretical model to assess whether the potential donor's attitudes towards organ donation (moral and human conviction, fear of physician negligence, and fear of mutilation of the body) and their religiosity influence the intentions of donating organs and talking to the family about donating organs, and these are the real conversation behavior. Finally, we consider the moderating role of the spokesperson of the message in the model, assessing ten possible spokespersons: physician, nurse, transplanted and spokespersons without identification (one female and one male for each of it) and also a priest and a nun. Regarding the methods, we conducted the study in two stages, a qualitative and complimentary exploratory research, with interviews and participant observation, which contributed to the construction of the conceptual model, and quantitative research to test the model, conducted in two stages, with data collection on attitudes, religiosity and intention first, followed by data collection on the realization of the expected behavior of conversation with the family. The data obtained were analyzed in three stages, with a final sample of 506 young respondents. Our results gave evidence that the attitudinal variables Moral and Human Conviction, Fear of Physician Negligence, and Fear of Mutilation of the Body influence the intention to donate and talk to the family about organ donation, as well as the real behavior of young people. The intentional variables were also confirmed as mediators of the model. Furthermore, the results show that nurses are the only spokesperson that influences the relationship between attitude and real behavior mediated by intentional factors, being, therefore, the spokesperson suggested to communicate the importance of talking with the family about organ donation with a positive focus on aspects related to the moral and human conviction of young Brazilians, above all.